Fecal culture and two fecal-PCR methods for the diagnosis of Mycobacterium avium subsp. paratuberculosis in a seropositive herd - Correa Valencia, Nathalia M.; Ramírez, Nicolás F.; Bülte, Michael; Fernández Silva, Jorge A. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: paratuberculosis is a slow-developing infectious disease, characterized by chronic granulomatous enterocolitis. This disease has a variable incubation period from 6 months to over 15 years, and is caused by Mycobacterium avium subsp. paratuberculosis (MAP). Its detection by direct and indirect diagnostic techniques has been of special interest. Objective: to report the diagnosis and detection of MAP using several diagnostic tests in a herd of the Northern region of Antioquia, Colombia. Methods: serum samples from the study herd were analyzed, using a commercial ELISA (enzyme-linked immunosorbent assay) kit. Fecal samples were cultured by duplicate using Herrold´s egg yolk medium (HEYM), and analyzed by an endpoint IS900-specific nested PCR protocol, and a commercial F57-real-time PCR kit. Results: eight out of 27 serum samples in the study herd resulted ELISA-positive. None of fecal samples resulted positive to HEYM culture by duplicate and none were found to be positive by F57-real-time PCR. Seven of the 27 fecal samples were found to be positive by end-point IS900-specific nested PCR. Agreement was found between ELISA and end-point IS900-specific nested PCR in one of the animals. Conclusion: the present study gives information about the agreement between direct and indirect MAP-detection techniques, using different matrixes from animals under the same husbandry conditions.